2016
DOI: 10.1080/01488376.2016.1235069
|View full text |Cite
|
Sign up to set email alerts
|

Paternal Multiple Partner Fertility and Environmental Chaos Among Unmarried Nonresident Fathers

Abstract: This study examined the association between paternal multiple partner fertility (MPF; having children with two or more partners) and indicators of environmental chaos (partnership instability, residential instability, work stability, material hardship, and perceived social support) among unmarried, non-resident fathers. Survey data from the Fragile Families and Child Wellbeing Study (N = 873) were used to compare unmarried non-resident fathers who experienced MPF to those who had children with one partner. Res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 51 publications
0
9
0
Order By: Relevance
“…For example, if fathers handle their stress by engaging in behaviors that diverge from family, cultural, and community norms, the mother may feel that it is in her best interest and the best interest of the child to remain distant. Similarly, when fathers' behaviors contribute to family disorder (i.e., home confusion and disorganization), children have elevated behavior problems, and parents engage in less effective discipline strategies (Dumas et al, 2005;Petren, 2017). Previous research has shown that the effects of parenting interventions are compromised when parents cannot work as a team to implement the program (Dush et al, 2011), highlighting the importance of making sure that both parents have the requisite co-parenting skills (Pearson et al, 2020).…”
Section: Individual Influencesmentioning
confidence: 99%
“…For example, if fathers handle their stress by engaging in behaviors that diverge from family, cultural, and community norms, the mother may feel that it is in her best interest and the best interest of the child to remain distant. Similarly, when fathers' behaviors contribute to family disorder (i.e., home confusion and disorganization), children have elevated behavior problems, and parents engage in less effective discipline strategies (Dumas et al, 2005;Petren, 2017). Previous research has shown that the effects of parenting interventions are compromised when parents cannot work as a team to implement the program (Dush et al, 2011), highlighting the importance of making sure that both parents have the requisite co-parenting skills (Pearson et al, 2020).…”
Section: Individual Influencesmentioning
confidence: 99%
“…Additionally, many researchers writing about multipartnered fertility and complex families have been concerned about the more general disadvantages associated with growing up in these types of situations, including worse educational outcomes (Bernardi and Radl 2014 ; Bronte-Tinkew et al 2009 ; Fomby and Osborne 2017 ; Fomby et al 2016 ; McLanahan et al 2013 ; Tach et al 2010 ). A common argument is that the complexity of such arrangements leads to considerable stress for both children and parents (Petren 2017 ). We argue that these negative effects are likely to work in the same direction as union dissolutions, affecting children of the first set negatively, because we expect the second union to provide a more stable environment (Beaujouan 2016 ; Poortman and Lyngstad 2007 ).…”
Section: Theory and Previous Researchmentioning
confidence: 99%
“…We include these controls given their interrelatedness and how they beget social and economic disadvantage and complexity. For instance, multiple partner fertility (MPF) is associated with partnership instability, residential instability, work instability, and material hardship among nonresident fathers (Petren, 2017). Fathers experiencing MPF are less accessible and less engaged with their children (McLeod & Tirmazi, 2017).…”
Section: Control Variablesmentioning
confidence: 99%